The Potsdam radon communication manifesto. Issue 7 (3rd July 2021) - Bouder, F.; Perko, T.; Lofstedt, R.; Renn, O.; Rossmann, C.; Hevey, D.; Siegrist, M.; Ringer, W.; Pölzl-Viol, C.; Dowdall, A.; Fojtíková, I.; Barazza, F.; et al.
Abstract: Risk communication efforts to mitigate the second cause of lung cancer worldwide (after tobacco smoking) – the radioactive gas radon in buildings – are often ineffective. Therefore, new European legal requirements bind member states to prepare communication strategies to '… increase public awareness and inform local decision makers, employers and employees of the risks of radon…' (Council directive 2013/59/EURATOM, ANNEX XVIII/(10)). This manifesto is written to support states to prepare an effective and efficient communication strategy and to avoid the main pitfalls in radon communication. It is based on the discussions that took place at a Workshop on Radon Risk Communication, organized by the German Federal Office of Radiation Protection (BfS) and hosted by the Institute for Advanced Sustainability Studies IASS in Potsdam, Germany from 8 to 10 of October 2019. The authors present a strategic view on the concrete measures that may be taken by authorities, experts and scientists to communicate the risk of radon to human health and to promote radon protection actions more effectively.